2020
DOI: 10.1155/2020/1618767
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Auricular Therapy for Cancer Pain: A Systematic Review and Meta‐Analysis

Abstract: Objective. This study aims to systematically assess the efficacy and safety of auricular therapy for cancer pain. Methods. A systematic search was conducted using PubMed, EMBASE, Cochrane library databases, CNKI, VIP, WanFang Data, and CBM for randomized controlled trials (RCTs). Review Manager 5.3 was used for meta-analysis. Results. Of the 275 screened studies, nine RCTs involving 783 patients with cancer pain were systematically reviewed. Compared with drug therapy, auricular therapy plus drug therapy has s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 25 publications
2
20
0
3
Order By: Relevance
“…In regards to oncology, in line with similar experiences reported in the literature [38][39][40], experts in our survey believe that CAM is useful to reduce collateral and adverse events during cancer chemo-and/or radiotherapy, as well as to give psychological support to the patients. CAMs are not considered as a therapy for the modification of the natural history of the pathology nor to prevent metastatic diffusion.…”
Section: Discussionsupporting
confidence: 81%
“…In regards to oncology, in line with similar experiences reported in the literature [38][39][40], experts in our survey believe that CAM is useful to reduce collateral and adverse events during cancer chemo-and/or radiotherapy, as well as to give psychological support to the patients. CAMs are not considered as a therapy for the modification of the natural history of the pathology nor to prevent metastatic diffusion.…”
Section: Discussionsupporting
confidence: 81%
“…Therefore, auricular acupuncture is easier to implement in clinical settings than body acupuncture. In oncology, auricular therapy has been studiedespecially in the treatment of cancer-related pain, but also for constipation-and appears to be effective and safe [33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…VAS is commonly used in pain evaluation. Previous studies [ 56 ] have suggested that the subjectivity and multidimensionality of pain experience produce individual differences in pain assessment. Some studies showed that analgesic requirements are controlled by healthcare providers and are directly affected by the types of surgery and the economic status of patients.…”
Section: Discussionmentioning
confidence: 99%